Comparative Analysis of Seed Transcriptome and Coexpression Analysis Reveal Candidate Genes for Enhancing Seed Size/Weight in Brassica juncea - Mathur, Shikha; Paritosh, Kumar; Tandon, Rajesh; Pental, Deepak; Pradhan, Akshay K. (Frontiers in Genetics, 2022)
Seed size/weight is a multigenic trait that is governed by complex transcriptional regulatory pathways. An understanding of the genetic basis of seed size is of great interest in the improvement of seed yield and quality in oilseed crops. A global transcriptome analysis was performed at the initial stages of seed development in two lines of Brassica juncea, small-seeded EH-2 and large-seeded PJ. The anatomical analyses revealed significant differences in cell number and cell size in the outer layer of the seed coat between EH-2 and PJ. Pairwise comparisons at each developmental stage identified 5,974 differentially expressed genes (DEGs) between the two lines, of which 954 genes belong to different families of transcription factors. Two modules were found to be significantly correlated with an increased seed size using weighted gene coexpression network analysis. The DEG and coexpression datasets were integrated with the thousand seed weight (Tsw) quantitative trait loci (QTL) mapped earlier in the EPJ (EH-2 × PJ) doubled haploid (DH) population, which identified forty potential key components controlling seed size. The candidate genes included genes regulating the cell cycle, cell wall biogenesis/modification, solute/sugar transport, and hormone signaling. The results provide a valuable resource to widen the current understanding of regulatory mechanisms underlying seed size in B. juncea.